2001
DOI: 10.1029/2001ja900032
|View full text |Cite
|
Sign up to set email alerts
|

Generation of atmospheric gravity waves associated with auroral activity in the polar F region

Abstract: Abstract. Relations between auroral activities and the generation of neutral-wind oscillations in the polar F region (150-300 kin) were investigated using data from the European Incoherent Scatter (EISCAT) radar, the all-sky auroral camera, and the IMAGE (International Monitor for Auroral Geomagnetic Effects) magnetograms. We dealt with two cases: observations on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Our observations suggest that large vertical winds may occur at intervals of high-temporal variation in Joule heating. This was not explored in the modelling study of Oyama et al (2001). Our experiment appears to provide the first evidence that meso-scale variability must be taken into account when calculating Joule heating.…”
Section: The Tristatic Experimentsmentioning
confidence: 98%
See 1 more Smart Citation
“…Our observations suggest that large vertical winds may occur at intervals of high-temporal variation in Joule heating. This was not explored in the modelling study of Oyama et al (2001). Our experiment appears to provide the first evidence that meso-scale variability must be taken into account when calculating Joule heating.…”
Section: The Tristatic Experimentsmentioning
confidence: 98%
“…As stated previously, Shinagawa et al (2003) carried out a modelling study of vertical winds generated by a moving auroral arc based on an EISCAT experiment by Oyama et al (2001). The study produced maximum vertical winds of 20 m/s, which were considerably less than the observations, and the authors acknowledge the need for a larger energy flux.…”
Section: The Tristatic Experimentsmentioning
confidence: 99%
“…At high latitudes, Samson et al (1990) suggested that the AGWs observed by SuperDARN originate near the ionospheric convection reversal boundary. Thus, it has been hypothesized that the IMF variations that lead to auroral electrojet fluctuations generate AGWs/TIDs, but the actual identification of the distant sources of the observed TIDs has posed difficulties in spite of the use of various observation techniques (Lewis et al, 1996;MacDougall et al, 1997;Hall et al, 1999, Oyama et al, 2001. One of the advantages of SuperDARN for the study of gravity waves is that it allows simultaneous observations of TIDs and of their high-latitude source activity.…”
Section: Introductionmentioning
confidence: 99%
“…Both the auroral activity (e.g. Hunsucker, 1982, Lewis et al, 1996Oyama et al, 2001) and tropospheric weather disturbances (e.g. Bertin et al, 1975;Waldock and Jones, 1987;Oliver et al, 1997) can generate medium-scale AGWs, particularly for TIDs that are observed at middle latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that highlatitude AGW sources are localized in or near the auroral oval (e.g. Sakanoi and Fukunishi, 1999;Oyama et al, 2001). Pervious statistical investigations also revealed that polar cap gravity waves frequently originate from sources in or near the midnight-dawn auroral oval (Innis and Conde, 2002) and that the horizontal phase progression is from the nightside to the dayside (Johnson et al, 1995).…”
Section: Properties Of the Polar Cap Agw/tidmentioning
confidence: 99%